E.H. Vestine papers - Vestine, E. H. (Ernest Harry), 1906-1968.
Correspondence, writings, reports, printed matter, and other papers concerning Vestine's career as a physicist and his work on geomagnetics, seismology, and cosmic rays with the Carnegie Institution of Washington and the Rand Corporation. Documents his activities with the International Scientific Radio Union, National Research Council (U.S.). Committee for International Year of the Quiet Sun, National Research Council (U.S.) Geophysics Research Board, and World Magnetic Survey Board. Subjects include the International Geophysical Year, 1957-1958, and the International Years of the Quiet Sun, 1964-1965. Correspondents include scientists from Australia, England, Japan, and the Soviet Union.
Physicist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Carnegie Institution of Washington; Rand Corporation; International Scientific Radio Union; National Research Council (U.S.). -- Committee for International Year of the Quiet Sun; National Research Council (U.S.). -- Geophysics Research Board; World Magnetic Survey Board; Cosmic rays; Electromagnetic fields; Geomagnetism; Geophysics -- International cooperation; International Geophysical Year, 1957-1958.; International Years of the Quiet Sun, 1964-1965.; Physics; Science -- International cooperation; Scientists -- Australia -- Correspondence; Scientists -- England -- Correspondence; Scientists -- Japan -- Correspondence; Scientists -- Soviet Union -- Correspondence; Seismology; Physicists